Pengaruh case based learning terhadap hasil belajar kognitif mahasiswa ditinjau dari computational thinking - Ira Wati Subandi; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2025)
The case-based learning model provides students with the opportunity to be effectively involved in the learning process so that they can construct their own knowledge. The purpose of this study was to determine the effect of case-based learning models on students' cognitive learning outcomes in terms of computational thinking. This study is a quantitative study. The sample was selected using cluster random sampling techniques. Data collection was carried out using essay test techniques to measure cognitive learning outcomes and computational thinking, as well as a scale to measure the level of student preference for learning. Validity testing was carried out using Aiken's V validity. Data analysis was carried out using Analysis of Variance (ANOVA). The results of this study are as follows. The results showed a positive effect of case-based learning models on the cognitive learning outcomes of UNS PGSD students. There was no significant effect between students' computational thinking and their cognitive learning outcomes. There was no interaction between case-based learning models and computational thinking skills with the cognitive learning outcomes of UNS PGSD students. Based on these results, it can be concluded that case-based learning models have an effect on students' cognitive learning outcomes. However, there was no effect between learning outcomes and computational thinking skills, and there was no interaction between case-based learning models and students' computational thinking skills. The results of this study can be used as a reference for further research.